Season Exerts Differential Effects of Ocean Acidification and Warming on Growth and Carbon Metabolism of the Seaweed Fucus vesiculosus in the Western Baltic Sea - Graiff, Angelika; Bartsch, Inka; Ruth, Wolfgang; Wahl, Martin; Karsten, Ulf (Frontiers in Marine Science, 2015)
Warming and acidification of the oceans as a consequence of increasing CO2-concentrations occur at large scales. Numerous studies have shown the impact of single stressors on individual species. However, studies on the combined effect of multiple stressors on a multi-species assemblage, which is ecologically much more realistic and relevant, are still scarce. Therefore, we orthogonally crossed the two factors warming and acidification in mesocosm experiments and studied their single and combined impact on the brown alga Fucus vesiculosus associated with its natural community (epiphytes and mesograzers) in the Baltic Sea in all seasons (from April 2013 to April 2014). We superimposed our treatment factors onto the natural fluctuations of all environmental variables present in the Benthocosms in so-called delta-treatments. Thereby we compared the physiological responses of F. vesiculosus (growth and metabolites) to the single and combined effects of natural Kiel Fjord temperatures and pCO2 conditions with a 5 °C temperature increase and/or pCO2 increase treatment (1100 ppm in the headspace above the mesocosms). Responses were also related to the factor photoperiod which changes over the course of the year. Our results demonstrate complex seasonal pattern. Elevated pCO2 positively affected growth of F. vesiculosus alone and/or interactively with warming. The response direction (additive, synergistic or antagonistic), however, depended on season and daylength. The effects were most obvious when plants were actively growing during spring and early summer. Our study revealed for the first time that it is crucial to always consider the impact of variable environmental conditions throughout all seasons. In summary, our study indicates that in future F. vesiculosus will be more affected by detrimental summer heat-waves than by ocean acidification although the latter consequently enhances growth throughout the year. The mainly negative influence of rising temperatures on the physiology of this keystone macroalga may alter and/or hamper its ecological functions in the shallow coastal ecosystem of the Baltic Sea.